Overview of NFPA 502 Standard for Road Tunnels, Bridges and Other Limited Access Highways, 2008 Edition - William Connell (Society for Mining, Metallurgy & Exploration, 2008)
NFPA 502, Standard for Road Tunnels, Bridges and Other Limited Access Highways establishes minimum fire protection and fire life safety requirements for road tunnels, bridges and other roadways where access by emergency responders is physically limited. The 2008 edition of NFPA 502 represents the Technical Committee?s consensus of current best practice for fire protection and life safety requirements for road tunnels, bridges and similarly limited access highways. Research of national and international test programs, design guidelines and regulating standards was per-formed and considered in an effort to establish a singular, comprehensive document representing a recognized base threshold of fire safety in these type facilities. This paper provides an overview of the more significant revisions including the application of fixed fire suppression systems, guidance on tenable environment, protection of structure and dangerous goods transport.